The effect of the feedback method on the obstetrics-gynecology residents’ learning in the management of early postpartum hemorrhage - Mahnaz Boroumand Rezazadeh; Tina Zeraati; Seyed Reza Mousavi; Nayereh Ghomian; Leyli Hafizi; Tayebeh Seyfizadeh; Mona Najaf Najafi; Majid Khadem-Rezaiyan (Research and Development in Medical Education)
Background: Simulation training, a novel learning method, provides medical students with opportunities to practice managing stressful situations as if they were experiencing them in reality. Recently, there has been increased recognition of the value of simulation-based education. This study aimed to evaluate the most effective approach for providing feedback during a simulation program. Methods: In this interventional study, a total of 43 obstetrics and gynecology residents were recruited and stratified into three groups based on their residency stage. These residents participated in a simulation-based program focused on the management of post-partum hemorrhage (PPH). The program involved handling a PPH scenario, during which they received feedback either during the task (in-task; IT) or after completing the task (end-task; ET). Following the simulation, a post-test was administered, and the results were compared between the IT and ET feedback groups. Results: Demographic variables did not differ significantly between the ET and IT groups. Generally, there were no significant differences in secondary knowledge (P=0.232) or secondary performance (P=0.196) following the simulation program between the two groups. However, Among second-year residents, the change in primary and secondary performance was not significant in either the ET (P=0.76) or IT (P=0.74) group, while the IT group showed a significant improvement in knowledge (P=0.04). For third-year residents, the point change in primary and secondary knowledge and performance was not statistically significant in either the ET or IT groups. Conclusion: The final knowledge and performance following simulation programs do not significantly differ between the IT and ET groups. However, second-year residents experienced an improvement in knowledge.